Pore water geochemistry of surface sediment recovered during SONNE cruise SO277 (Mediterranean Sea) - Mark Schmidt (PANGAEA, 2025)
Data set comprises pore water chemistry and sediment physical properties of sediment cores recovered by gravity coring (GC) during SO277 cruise off Malta (Berndt et al., 2021). Gravity coring was conducted between 14.08. and 03.10.2020 east of Malta and east of Sicily in the Mediterranean Sea and Ionian Sea, respectively, to investigate fluid release spots induced by gas and/or freshened groundwater advection.